2017
DOI: 10.1080/02726351.2017.1321073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction between polymer and surfactant in aqueous solutions for chemical-enhanced oil recovery

Abstract: Most petroleum reservoirs are subjected to Improved and Enhanced Oil Recovery (IOR and EOR) processes following secondary recovery. EOR involves the application of external forces and substances to improve the chemical and physical interactions in hydrocarbon reservoirs in order to improve preferable recovery conditions. The process of chemical flooding with solutions of polymers and surfactants can be used for developing oil exploitation. Studying the interaction between surfactants and polymers is indispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is observed that viscosity of copolymer solutions increases with increasing concentration. This suggests the formation of interchain and intrachain aggregates caused by entanglement of HMPA hydrophobe chains. , However, in gemini surfactant + copolymer-based systems, surfactant micelles associate with polymer chains described as a “string of beads model” owing to the improved hydrophobic interaction effect . In the presence of 14-6-14 GS, cationic head groups enhanced the electrostatic forces existing among the polymer-surfactant molecule.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that viscosity of copolymer solutions increases with increasing concentration. This suggests the formation of interchain and intrachain aggregates caused by entanglement of HMPA hydrophobe chains. , However, in gemini surfactant + copolymer-based systems, surfactant micelles associate with polymer chains described as a “string of beads model” owing to the improved hydrophobic interaction effect . In the presence of 14-6-14 GS, cationic head groups enhanced the electrostatic forces existing among the polymer-surfactant molecule.…”
Section: Results and Discussionmentioning
confidence: 99%
“…25 Kothencz et al and others and Al-Sabagh et al also studied the interaction between polymer chains and surfactant micelles/molecules and optimized fluid compositions to control their relative effects on mixed polymer-surfactant systems. 26,27 Surfactant-polymer systems are functional in situations wherein high tolerance to salt is necessary. The synergistic interactions between the polymer and surfactant play a pivotal role in understanding mechanistic interactions, as well as devising/optimizing novel chemical displacing fluids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In EOR processes, surfactant fluids recover residual oil molecules by interfacial tension (IFT) reduction. Previous studies reported that the IFT between oil and displacing fluid must decrease to ultralow magnitudes for displacement of in situ oil from pore spaces (otherwise trapped by capillary forces) of hydrocarbon-bearing reservoir rocks. , Surfactant monomers are adsorbed onto the oil/aqueous interfaces, with the hydrophobic tail groups orienting toward the oil phase and hydrophilic heads pointing toward the aqueous phase. This results in micelle/aggregate formation, which is an important transport conduit for crude oil movement. , Mixed surfactant fluids improve the oil micellization ability of constituent surfactants by forming mixed micelles in dynamic flow systems. Incorporation of ionic + nonionic surfactants into aqueous fluids reduce the repulsive interactions among charged polar head groups and favors improved adsorption efficiencies, which in turn is responsible for improved oil extraction. Earlier studies showed that binary surfactant mixtures exhibit lower critical micelle concentration (CMC) values in comparison to single surfactants alone. The neutral head groups in nonionic surfactant molecules impart a blanketing effect on the ionic surfactant head groups, thereby leading to the formation of condensed/denser micellar structures with greater stability .…”
Section: Introductionmentioning
confidence: 99%
“…The average hydrodynamic radii ( D h ) were measured using the dynamic light scattering. Polymer solution was dedusted and filtered using a disposable 0.8‐μm filter purchased from Millipore corporation . In the measuring process, a 532 nm laser wavelength was used.…”
Section: Methodsmentioning
confidence: 99%